The true confessions of charlotte doyle eaudiobook - Avi (Recorded Books Inc., 2013)
Avi's swashbuckling tale of murder and mutiny on the high seas has a fascinating twist: the heroine is a 13-year-old girl. In 1832, Charlotte Doyle boards a ship bound for America and is caught in a battle between a mad captain and his ruthless crew. If you're looking for an action-packed adventure story for girls, you'll find it in The True Confessions of Charlotte Doyle.